Banking risks around the world : the implicit safety net subsidy approach - Laeven, Luc (Policy research working paper, 2000)
The degree of risk taking by a bank is related to the size of the gross subsidy that has been extended to the bank by the safety net. This subsidy can be calculated by applying a technique that models deposit insurance as a put option on the bank's assets